Sinergitas Guru dan Orang Tua dalam Menumbuhkan Minat Belajar Anak di Lembaga Pendidikan Madrasah Ibtidaiyah Bustanul Ulum - M.Bustanul Ulum (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The Covid-19 pandemic period has not yet passed, the world of education is in a polemic between complying with government regulatory policies and the importance of learning for the nation's young generation, which until now are still doing online learning. There are many pros and cons in dealing with this. Then a number of problems arise and one of the problems we often see today is the declining interest in children's learning and the lack of support from parents. Interest in learning decreased due to students experiencing boredom in online learning. Besides that, face-to-face learning is considered more capable of boosting children's interest in learning, as well as fostering a high understanding of the learning material presented by the teacher. Technological tools in the form of mobile phones as a source of children's learning are not maximally able to foster children's interest in learning. They more often use mobile phones as a tool to play and play, learning is no longer efficient. As an educator, I must be able to build synergy with students and also their parents and the surrounding community. And one of the synergies that have been built is in the form of an organization, because in my opinion, from the several approach strategies that I have taken, Gratefuly, there have been significant changes. This also happened because of the support from parents. Keywords: Synergy, Interest in Learning, Parental Support, Planning